Ammonia emissions from China-6 compliant gasoline vehicles tested over the WLTC. (15th February 2019) - Wang, Xin; Ge, Yunshan; Gong, Huiming; Yang, Zhengjun; Tan, Jianwei; Hao, Lijun; Su, Sheng
Abstract: Ammonia emissions cause several negative impacts on the quality of air, water and soil, while secondary ammonia formed on three-way catalysts (TWCs) of gasoline vehicles has not been sufficiently investigated, especially in the developing countries. In this paper, tailpipe ammonia emissions from seven China-6 certified, low-mileage gasoline vehicles were measured over the World Harmonized Light-duty Test Cycle (WLTC). The results demonstrated that ammonia emissions from the seven test vehicles ranged from 0.65 ± 0.38 mg/km to 8.01 ± 3.12 mg/km. A comparison with the emission factors reported in other research indicates that these China-6 certified vehicles emitted similar or less ammonia emissions compared to the vehicles certified to older EU and federal regulations. The ammonia emissions from the test vehicles showed very weak linkage with their engine or transmission technologies. For all the test vehicles, the vast majority of ammonia emissions were emitted within the engine warm-up period due to already lighted-off catalysts but still enriched air/fuel mixtures. No ammonia emissions were noticed within any engine-start events. The masses of ammonia-converted ammonium salts were estimated assuming that all the tailpipe ammonia emissions will transform into ammonium nitrate and ammonium sulfate, and compared to the primary PM emissions measured with filters. The masses of salts were drastically higher than the primary PM, which underscored the significance of vehicle-related ammonia emissions as a key ambient PM contributor. Highlights: Ammonia emissions from 7 China-6 compliant cars were measured over the WLTC. Ammonia ranged from 0.65 ± 0.38 to 8.01 ± 3.12 mg/km, smaller than older vehicles. The vast majority of ammonia was found within the engine warm-up period. Ammonia formed on catalysts may cause stronger contamination than tailpipe PM.